Cleaning up the environment in juvenile myelomonocytic leukemia - Deng, Lisa; Chan, Rebecca J. (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Juvenile myelomonocytic leukemia (JMML) is a commonly fatal myeloid leukemia occurring in very young children bearing germline or somatic mutations in genes within the RAS-ERK signaling pathway including NF1, CBL, KRAS, NRAS, and PTPN11 (1). Leukemia relapse following allogeneic stem cell transplant is uncharacteristically high at 40–50% for JMML patients, and findings from the recently published manuscript by Dong et al.